Personalized medicine to treat refractory benign paroxysmal positional vertigo, through computational fluid dynamics analysis from magnetic resonance image reconstructions - Rossi-Izquierdo, Marcos; Santos-Pérez, Sofia; Arán-Tapia, Ismael; Blanco-Ulla, Miguel; Arán-González, Ismael; Vaamonde-Sánchez-Andrade, Isabel; Franco-Gutiérrez, Virginia; Pérez-Muñuzuri, Vicente; Muñuzuri, Alberto P.; Soto-Varela, Andrés (Frontiers in Neurology, 2025)
BackgroundBenign paroxysmal positional vertigo (BPPV) is the most common cause of vertigo, often effectively treated with standard canalith repositioning maneuvers (CRMs). However, approximately 12.5% of cases remain refractory, leading to persistent symptoms and increased healthcare burden. Variations in the anatomical orientation of the semicircular canals (SCCs) may explain the resistance to conventional maneuvers. This study explores a personalized medicine approach, utilizing computational fluid dynamics (CFD) based on MRI reconstructions to tailor CRMs with the help of mechanical rotation chair according to individual inner ear anatomy.MethodsWe conducted a randomized, multicenter, open-label study targeting patients with refractory posterior canal BPPV. Participants were allocated to either a control group (receiving repeated standard CRMs and Brandt-Daroff exercises) or an intervention group (receiving personalized CRMs based on CFD simulations derived from MRI scans). The intervention group’s maneuvers were executed using a mechanical rotational chair designed for precise angulation. Primary outcomes included resolution of nystagmus and vertigo symptoms, while secondary outcomes measured the reduction in healthcare visits and improved quality of life (Dizziness Handicap Inventory score).DiscussionPersonalized CRMs based on CFD models may enhance treatment efficacy for refractory BPPV by optimizing maneuver angles according to the specific SCC orientation. This approach could significantly reduce symptom persistence, decrease the need for repeated healthcare visits, and improve patient outcomes. The use of non-invasive MRI and CFD techniques represents a novel step toward individualized treatment in vestibular disorders, with potential for broader application in personalized otoneurology. Further analysis will determine the extent of clinical benefit and cost-effectiveness of this approach.Clinical trial registrationClinicalTrials.gov, Identifier: NCT06725966.